Environment Friendly Technologies for Increasing Rice Productivity - Basnet, Bhola Man Singh (Journal of Agriculture and Environment, 2009)
Rice is one of the most important cereal crops in Nepal. As per the preliminary estimate of f.y.2007/08, the rice crop was grown in 1.55 million hectare producing 4.3 million mt and the productivity was 2.775 t/ha. It contributes nearly 20% to Agricultural Gross Domestic Product and provides more than 50% of the total calories required to the Nepalese people. The UNO also declared 2004, as the "International Year of Rice" with the theme "Rice is Life". There are less possibilities of bringing more lands into production. Therefore, we have to increase the productivity per hectare per day by any means .The promising technologies generated by agriculture research play the pivotal role for increasing rice productivity. Nepal so far has released fifty-six (56) rice varieties with full package of practices within the span of forty-one (41) years. The modern varieties can express their yield potentiality only when recommended packages are practiced. Quality seeds alone can contribute 15-20% yield. Early paddy and Boro (winter) rice can be used for increasing rice yields by utilizing higher intensity of solar radiation. The system of rice intensification (SRI) is the other agronomic manipulation, which can increase rice yield. Resource conservation technologies (RCTs) like dry seed-bed practice, direct seeded rice, zero-till, drought tolerant varieties, use of renewable energy and creating public awareness are to be followed so as to produce rice on environmeny-friendly ways. However, we should not forget the environment-friendly and sustainability issues while increasing the productivity and production. It is said "Grow Paddy with Soil Fertility, Wheat with Fertilizers", and "Healthy Seedlings are responsible at least for half of the yield" also. Worldwide food crisis and skyrocketed prices are the problems caused by climate change too. Key words: Environment-friendly, rice production, technology, integrated crop management The Journal of Agriculture and Environment Vol:.9, Jun.2008 page: 34-40